EFFECT OF ISOPROPYL ALCOHOL (C3H8O) MIXTURE WITH GASOLINE FUEL AGAINST EXHAUST GAS EMISSIONS IN 4 STEP COMBUSTION MOTORCYCLES - Fauzie, Amin; Aprilyanti, Selvia; Suryani, Faizah (TRAKSI, 2024)
This research was to analyze how much influence a mixture of isopropyl alcohol (IPA) with a purity content of 100% has on CO, CO2, 02, and HC exhaust gas levels. The research was carried out by varying the amount of isopropyl alcohol mixture 5, 10, 15, 20, 25 ml and motor engine speed 1000, 1500, 2000, 2500, 3000 Rpm. From the test results of the Honda Supra oxygen (O2), as follows: CO2 gas content= 0.093%, CO= 0.135%, HC = 17.80%. For research on exhaust emissions in 4-stroke motorbikes using gasoline without a mixture of isopropyl alcohol, the percentage increase in CO2 gas content= 0.10%, CO= 0.136%, HC= 18.62%. By mixing the fuel with isopropyl alcohol, the combustion process of a motorbike has good prospects as a mixture that can influence the results of the combustion process of a motorbike on exhaust gas emissions (environmentally friendly). Mixing 4 stroke motorbike fuel with isopropyl alcohol will cause the octane number to increase, so that fuel use in the internal combustion will become more economical.